Orbital interactions in chemistry - Albright, Thomas A.; Burdett, Jeremy K., 1947-; Whangbo, Myung-Hwan. (Hoboken, New Jersey : John Wiley, 2013)
"This new edition of a bestselling reference on applied molecular orbital theory covers organic, organometallic, inorganic, and solid state chemistry, demonstrating how common orbital situations arise through the whole chemical spectrum. This latest edition features a new chapter on current concepts in solid state chemistry, examples of recent advances in the field, more detailed information on trends in the periodic table, expanded information on the mechanics of group theory, and a new chapter on metals. An essential reference for chemists in the areas of organic, inorganic, solid state, and computational chemistry"--
Includes index.
Includes bibliographical references and index.
Keywords: Molecular orbitals; SCIENCE / Chemistry / Physical & Theoretical